Digital Media Platforms and Women’s Political Engagement in Southwest Nigeria - Bolanle Morenike Adeoluwa; Bankole Olagunju Faloye; Enioluwa Prince Adeoluwa; Olanike Justinah Olusola; Olaolu Olaruku Olaimolu (Universitas Negeri Yogyakarta, 2026)
The study examined digital media platforms and women’s political engagement in southwest Nigeria. The study adopts a descriptive survey research design. According to the National Population Commission (NPC) and National Bureau of Statistics (NBS), 2016 and 2023, the population of women in Ekiti State is estimated to be 1,553,770, while that of Lagos State is 5,956,115. The two states were randomly selected from the six states in southwest Nigeria. The sample of 400 was selected at random. The validity of the instrument was ascertained by using face and content validity. Cronbach’s Alpha method was used to test the internal consistency of the instrument, and a coefficient of 0.98 was obtained, which indicates that the instrument was reliable to collect data for the study. The research questions were answered using descriptive statistics such as frequency, percentage, mean, and standard deviation. Findings revealed that the women from Lagos and Ekiti States affirm that they use Facebook, X (formerly Twitter), WhatsApp, YouTube, and Snapchat more than other social media platforms such as LinkedIn, TikTok, and WeChat. The study concluded that digital media platforms significantly influence digital media usage by women for socio-political engagement in Southwest Nigeria. Therefore, the study recommended that these platforms should be widely promoted among women in Lagos and Ekiti States to promote socio-political participation.